Identification and functional analysis of ZmDLS associated with the response to biotic stress in maize - Wang, Yiting; Zou, Jie; Li, Jiali; Kong, Fanna; Xu, Lina; Xu, Dafeng; Li, Jiaxin; Yang, Huaying; Zhang, Lin; Li, Tingchun; Fan, Honghong (Frontiers in Plant Science, 2023)
Terpenes are the main class of secondary metabolites in response to pests and germs attacks. In maize (Zea mays L.), they are the essential components of the herbivore-induced plant volatile mixture, which functioned as a direct or indirect defense against pests and germs attacks. In this study, 43 maize terpene synthase gene (ZmTPS) family members were systematically identified and analyzed through the whole genomes in maize. Nine genes, including Zm00001d032230, Zm00001d045054, Zm00001d024486, Zm00001d004279, Zm00001d002351, Zm00001d002350, Zm00001d053916, Zm00001d015053, and Zm00001d015054 were isolated for their differential expression pattern in leaves after corn borer (Ostrinia nubilalis) bite. And six genes (Zm00001d045054, Zm00001d024486, Zm00001d002351, Zm00001d002350, Zm00001d015053, and Zm00001d015054) were significantly up-regulated in response to corn borer bite. Among them, Zm00001d045054 was cloned. Heterologous expression and enzyme activity assays revealed that Zm00001d045054 functioned as D-limonene synthase. It was renamed ZmDLS. Further analysis demonstrated that its expression was up-regulated in response to corn borer bite and Fusarium graminearum attack. The mutant of ZmDLS down-regulated the expressions of Zm00001d024486, Zm00001d002351, Zm00001d002350, Zm00001d015053, and Zm00001d015054. It was more attractive to corn borer bite and more susceptible to F. graminearum infection. The yeast one hybrid assay and dual-luciferase assay showed that ZmMYB76 and ZmMYB101 could up-regulate the expression of ZmDLS by binding to the promoter region. This study may provide a theoretical basis for the functional analysis and transcriptional regulation of terpene synthase genes in crops.